Panorama do uso de serviços hospitalares nos últimos anos de vida em pessoas que vivem com demência - Silva, Thaís Barros Pereira da (Universidade Federal de São Carlos, 2026)
Introduction: The end-of-life period for people living with dementia is often marked by intensive use of hospital services. However, evidence remains limited regarding how this diagnosis influences hospitalization trajectories, as well as which factors are associated with hospital transitions and the higher frequency and length of stay of these hospitalizations in the years preceding death in this population. Objectives: This dissertation has three objectives: (I) To compare trajectories of length of stay in the last four years of life between people living with and without dementia; (II) To investigate factors associated with hospital transitions in the last year of life in people living with dementia; and (III) To investigate factors associated with trajectories of the number and length of stay of unplanned hospitalizations in the last four years of life in people living with dementia. Methods: Participants were individuals aged 60 years or older from the English Longitudinal Study of Ageing (ELSA Study) with data linked to Hospital Episode Statistics (HES). For the first objective, trajectories of length of stay during the last four years of life were analyzed in 2,870 people living with and without dementia. To fulfill the second objective, a cross-sectional study was conducted involving 522 people living with dementia, where the outcome was hospital transition in the last year of life, defined by the occurrence of: 1) ≥ 1 hospitalization in the last three days of life; 2) discontinuity of care, before or after a hospitalization characterized by transfer between different care settings in the last 90 days of life; or 3) ≥ 2 hospitalizations in the last 90 days of life. The third objective investigated sociodemographic and clinical factors associated with trajectories of the number and length of stay of unplanned hospitalizations in 521 people living with dementia. Generalized Linear Mixed Models (GLMM) were used for trajectory analyses, while a logistic regression model was used for the cross-sectional analysis. Results: Regarding length of stay trajectories, in the last year of life, the length of stay was equal between people living with and without dementia. However, in the four previous years, the length of stay increased, on average, by 3.18 days per year (d/y) in people without dementia and 0.59 d/y in people living with dementia. The difference between groups (-2.59 d/y) demonstrated a higher rate of increase in length of stay for people without dementia, given that, four years before death, the average days of hospitalization for people living with dementia (24.99 days per year) was already higher than for those without dementia (16.99 days per year). Additionally, in people living with dementia, factors associated with hospital transition in the last year of life were: being male, higher socioeconomic deprivation, and having pneumonia and delirium. Finally, factors associated with an increase in the number of unplanned hospitalizations in participants living with dementia in the last four years of life were: higher socioeconomic deprivation, presence of urinary tract infection (UTI), and presence of acute myocardial infarction (AMI). Advanced age (≥70 years) was associated with longer length of stay. Conversely, factors associated with a reduction in the length of stay of unplanned hospitalizations were: hospital admissions for endocrine, nutritional, and metabolic diseases, and the presence of delirium. Conclusions: The length of stay was higher in people with dementia four years before death, but increased more among those without dementia as death approached, equalizing between both groups at the end of life. Hospital transition in the last year of life in people living with dementia was associated with being male, having higher socioeconomic deprivation, and presenting pneumonia and delirium. In the last four years of life, higher socioeconomic deprivation, UTI, and AMI increased the number of unplanned hospitalizations. During the same period, advanced age increased the length of stay, while admissions for endocrine, nutritional, and metabolic diseases and delirium decreased the length of stay of unplanned hospitalizations. Identifying the panorama of hospital service use in the last years of life for people living with dementia can inform advance care planning and contribute to better quality end-of-life care for this population.
Overview of hospital service use in the final years of life among people living with dementia
Keywords: Demência; Envelhecimento; Epidemiologia; Fim da vida; Internações hospitalares; Transição para o hospital; Dementia; Aging; Epidemiology; End-of-life; Hospitalizations; Hospital transition; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE::SAUDE COLETIVA; 3. Saúde e Bem-Estar